(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article analyzes the results of studying the level of awareness of teachers in the prevention of school myopia among students. This problem is highly relevant, since literary data and practice show that many healthy children go to the first grade and finish school when they acquire school myopia. In matters of prevention of school myopia, a large place is given to teachers of secondary schools. Therefore, the study of the level of awareness of teachers in the prevention of school myopia in children has exceptional knowledge. The results of the study indicate that of the 138 teachers surveyed in Yerevan, Gyumri and Charentsavan in secondary schools, the overwhelming majority (98,5%) emphasized the importance of carrying out work to prevent myopia in students. in practice, 31,9% of them purposefully and systematically do not carry out this work, 68,1% teachers do it on a case-by-case basis, monitoring the compliance of the students with the norms and correct work and rest the eyes. It is interesting to note that 63,7% teachers surveyed frankly acknowledged that their work on the prevention of school myopia among their students was unsatisfactory. It was also established that the interviewed teachers, when organizing and conducting work on the prevention of myopia, almost never use the scientific and methodological literature and this problem for their students, but rely only on their own knowledge and personal experience. So, the conducted study indicates a lack of awareness among the respondents of teachers about the prevention of school myopia among students. Along with this, unresolved problems were identified and the main directions of their solution were identified.